Validation of a clinicopathological score for the prediction of post-surgical evolution of pituitary adenoma: retrospective analysis on 566 patients from a tertiary care centre. Issue 2 (February 2019) - Asioli, S; Righi, A; Iommi, M; Baldovini, C; Ambrosi, F; Guaraldi, F; Zoli, M; Mazzatenta, D; Faustini-Fustini, M; Rucci, P; Giannini, C; Foschini, M P
Abstract : Objective and design: A clinicopathological score has been proposed by Trouillas et al . to predict the evolution of pituitary adenomas. Aim of our study was to perform an independent external validation of this score and identify other potential predictor of post-surgical outcome. Methods: The study sample included 566 patients with pituitary adenomas, specifically 253 FSH/LH-secreting, 147 GH-secreting, 85 PRL-secreting, 72 ACTH-secreting and 9 TSH-secreting tumours with at least 3-year post-surgical follow-up. Results: In 437 cases, pituitary adenomas were non-invasive, with low (grade 1a: 378 cases) or high (grade 1b: 59 cases) proliferative activity. In 129 cases, tumours were invasive, with low (grade 2a: 87 cases) or high (grade 2b: 42 cases) proliferative activity. During the follow-up (mean: 5.8 years), 60 patients developed disease recurrence or progression, with a total of 130 patients with pituitary disease at last follow-up. Univariate analysis demonstrated a significantly higher risk of disease persistence and recurrence/progression in patients with PRL-, ACTH- and FSH/LH-secreting tumours as compared to those with somatotroph tumours, and in those with high proliferative activity (grade 1b and 2b) or >1 cm diameter. Multivariate analysis confirmed tumour type and grade to be independent predictors of disease-free-survival. Tumour invasion, Ki-67 and tumour type were the only independent prognostic factors of disease-free survival. Conclusions: Our data confirmed the validity of Trouillas' score, being tumour type and grade independent predictors of disease evolution. Therefore, we recommend to always consider both features, together with tumour histological subtype, in the clinical setting to early identify patients at higher risk of recurrence.